Erotic Memoirs and Postfeminism - Gwynne, J. author. aut Link
VI, 126 p.
Keywords: This book analyses the impact of postfeminist discourse and the mainstreaming of pornography on our understanding of intimacy and female sexuality. It is a broad critical survey of a recent publishing phenomenon – the female-authored erotic memoir – and positions the texts under analysis as complex and contradictory expressions of popular feminism.